Binary‐Metal Perovskites Toward High‐Performance Planar‐Heterojunction Hybrid Solar Cells. (14th August 2014) - Zuo, Fan; Williams, Spencer T.; Liang, Po‐Wei; Chueh, Chu‐Chen; Liao, Chien‐Yi; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> A simple, low temperature solution process for Pb/Sn binary‐metal perovskite planar‐heterojunction solar cells is demonstrated. Sn inclusion substantially influences the band‐gap, crystallization kinetics, and thin‐film formation leading to a broadened light absorption and enhanced film coverage on ITO/PEDOT:PSS. As a result, the optimized device shows a PCE exceeding 10%, which is the best result for binary‐metal perovskite solar cells so far. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>